Mobile magnetic chip collector (2M2C) / Aznizam Abdullah … [et al.] - Abdullah, Aznizam; Hussain, Zakaria; Tazijan, Farina Nozakiah; Osman, Mohd Faizal; Mohd Kassim, Mohd Huda (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Engineering workshops in universities are usually fully occupied during the semester. Sessions are held back to back; maximizing the utilities. One of the problems faced by the students and staff is maintaining a clean workshop during and after the machining lessons. Most lecturers have to end their lessons and workshops early in order to make time for the cleaning process to take place. Cleaning up the chips is time consuming and tedious. In order to facilitate this problem, a mobile magnetic chip collector (2M2C) is being introduced. 2M2C is a semi-automated wheel mobile robot that operates to collect chips on dry or wet floor of the workshop. It is reported that MMC has help to manage time to clean workshops and has the potential to be commercialized.